Strangulated umbilical hernia in a peritoneal dialysis patient - Swarnalatha, G. (Medknow Publications & Media Pvt Ltd, 2012)
Hernia is one of the commonest complications of peritoneal dialysis. It is recommended that patients undergo surgical repair of hernias immediately after the diagnosis. We report a patient on continuous ambulatory peritoneal dialysis presenting with strangulated umbilical hernia. He underwent resection of the gangrenous ileum and end-to-end anastomosis. He was shifted to hemodialysis on second postoperative day and was continued on hemodialysis for 2 weeks. In the third week, he was initiated on low volume PD exchanges and by the fourth week, he returned to normal CAPD exchanges.